2022
DOI: 10.3390/land11020244
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Prediction of Carbon Storage Based on Land Use/Land Cover Dynamics in the Tropics: A Case Study of Hainan Island, China

Abstract: Land use and land cover (LULC) change in tropical regions can cause huge amounts of carbon loss and storage, thus significantly affecting the global climate. Due to the differences in natural and social conditions between regions, it is necessary to explore the correlation mechanism between LULC and carbon storage changes in tropical regions from a broader geographical perspective. This paper takes Hainan Island as the research object, through the integration of the CA-Markov and Integrated Valuation of Ecosys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 82 publications
(101 reference statements)
0
22
0
Order By: Relevance
“…Wang et al [37] used the PLUS and InVEST models to simulate changes in future land use patterns and the regional carbon storage capacity and found that scenario establishment had a significant influence on the accuracy and reliability of the simulation results. The coupled PLUS-InVEST model can be applied to simulate changes in land use and ES assessment to provide useful guidance for improving regional ESs [38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [37] used the PLUS and InVEST models to simulate changes in future land use patterns and the regional carbon storage capacity and found that scenario establishment had a significant influence on the accuracy and reliability of the simulation results. The coupled PLUS-InVEST model can be applied to simulate changes in land use and ES assessment to provide useful guidance for improving regional ESs [38].…”
Section: Introductionmentioning
confidence: 99%
“…Anhui Province is located in the hinterland of the Yangtze River Delta, with diverse landform types, abundant hydrothermal resources, and an outstanding ecological location. As urbanization and high-quality integrated development of the Yangtze River Delta have resulted in a sharp increase in environmental pressure, elucidating changes in ES functions is very useful for the green development of the region [38]. In this study the InVEST (v. 3.11.0) and PLUS (v. 1.3.6)…”
Section: Introductionmentioning
confidence: 99%
“…This model has been widely used by foreign scholars in many countries and important regions and has shown strong applicability in the research of China [10][11][12][13]. The scholars combined the model with land simulation models such as CA-Markov [14], Markov-CLUE-S [15], FLUS [16], and PLUS [17] to explore the future distribution of carbon storage. PLUS has a high precision in land simulation, which can add future factors to limit the prediction of land change, so as to explore the impact of climate change.…”
Section: Introductionmentioning
confidence: 99%
“…However, the carbon sink effect of each land-use type conversion varies in different regions and even shows carbon loss. Since this carbon sink process is complex and variable, it exhibits different evolutionary characteristics in different spatial and temporal contexts [ 7 , 8 ]. Therefore, it is also important to clarify the dynamic relationship between land-use changes and CS.…”
Section: Introductionmentioning
confidence: 99%